A Literature Review of Social and Economic Leader–Member Exchange - Andersen, Ingvild; Buch, Robert; Kuvaas, Bård (Frontiers in Psychology, 2020)
Leader member exchange (LMX) research has increasingly relied upon social exchange theory (SET) as a theoretical foundation, but the dominating way of measuring LMX have not followed this theoretical development (Gottfredson, Wright, & Heaphy, in press). With the aim of developing a measure that more coherently reflects SET, Kuvaas, Buch, Dysvik, and Haerem (2012) conceptualized LMX as two qualitatively different relationships, labelled economic LMX and social LMX. Since the most applied LMX measures are under scrutiny for not being sufficiently grounded in theory (Gottfredson et al., in press) it may be especially important to expose alternative measures. Therefore, we provide a comprehensive review of the research to date applying a two-dimensional approach to LMX, while also adding to interpretation and suggestions for how we can progress the field even further.